ANALISA FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA SYSTEM INFORMASI AKUNTANSI PADA CV WASTU DHARMA - Masroka Priyo Utomo, 0835030714; Maryono, Maryono (Students Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of accounting information system performance against user participation, top management support, training programs and personal capabilities of enterprise systems. Data were analyzed using multiple linear regression analysis (multiple regretion). The population in this study were all employees at CV Wastu Dharma Semarang by the number of 38 people all of whom are users of the accounting information system. Collection techniques by using purposive sampling technique sampilng which is subject to selection based on traits or characteristics specific properties determined researchers to achieve a certain goal (Sutrisno, 2000: pp82). Criteria sample is at least 1 year working period and a permanent employee at the CV Wastu Dharma Semarang. The number of samples used is up to 40 permanent employees. The amount is according opinion Bailey stating that studies using statistical data analysis, which used a minimum sample size is 30 (Iqbal Hasan M, 2002). Keywords: accounting information system performance, user participation, training, top management support, personal capability system.